Utilizing apolipoprotein E genotypes and associated comorbidities for the assessment of the risk for dementia - Tung, Hsin; Lin, Ching-Heng; Chen, Yi-Ming; Lee, Wei-Ju; Chien, Li-Sheng; Sun, Ting-Hsuan; Liao, Cai-Sian; Lin, Yung-Yang; Hsiao, Tzu-Hung (Frontiers in Aging Neuroscience, 2022)
Introduction Dementia is associated with many comorbidities while being related to Apolipoprotein E (ApoE) polymorphism. However, it is unclear how these clinical illnesses and genetic factors modify the dementia risk. Methods We enrolled 600 dementia cases and 6000 matched non-dementia controls, with identified ApoE genotype (ε4/ε4, ε4/ε3, and ε3/ε3). Eight comorbidities were selected by medical records, and counted if occurring within 3 years of enrollment. Results The dementia group had a higher ratio of carrying ε4 allele and prevalence of comorbidities than the non-dementia group. Homozygous ε4 carriers presented the broken line of dementia risk with the peak age at 65–75 years and odds ratio (OR) up to 6.6. The risk only emerged after 65 years of age in ε3/ε4 subjects with OR around 1.6–2.4 when aged > 75 years. Cerebrovascular accident (CVA) is the commonest comorbidity (14.6%). CVA, sleep disorder, and functional gastrointestinal disorders remained as significant risk comorbidities for dementia throughout all age groups (OR = 1.7–5.0). When functional gastrointestinal disorder and ε4 allele both occurred, the dementia risk exceeded the summation of individual risks (OR = 3.7 and 1.9 individually, OR = 6.0 for the combination). Comorbidities could also be predictors of dementia. Conclusion Combining the genetic and clinical information, we detected cognitive decline and optimize interventions early when the patients present a specific illness in a particular age and carry a specific ApoE allele. Of comorbidities, functional gastrointestinal disorder is the strongest predicting factor for dementia in ε4 allele carriers.